Relevant domains and outcome measurement instruments in neuropsychiatric systemic lupus erythematosus: a systematic literature review. (31st March 2021) - Silvagni, Ettore; Chessa, Elisabetta; Bergossi, Francesca; D'Amico, Maria Ester; Furini, Federica; Guerrini, Giulio; Cauli, Alberto; Scirè, Carlo Alberto; Bertsias, George; Govoni, Marcello; Piga, Matteo; Bortoluzzi, Alessandra
Abstract: Objectives: Although neuropsychiatric involvement in SLE (NPSLE) is one of the most complex and troubling manifestations of the disease, validated outcome instruments to be used as sensitive endpoints in controlled clinical trials are lacking. We performed a systematic literature review (SLR) to identify outcome measurement instruments and domains used to assess NPSLE. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were used. Articles available in English (1967–2020), listed in PubMed, Embase, PsycINFO, Cochrane Library and the EULAR outcome measures library were screened. All domains and outcome measurement instruments were characterized according to the OMERACT Filter 2.1, considering core areas (manifestations/abnormalities, life impact, death/lifespan, societal/resource use) and contextual factors. Results: Of 3392 abstracts evaluated, 83 studies were included in the SLR (15 974 patients, females 89.9%). Eligible studies included domains and instruments pertinent to all core areas defined by the OMERACT, except for 'societal/resource use'. The most common core areas were 'manifestations/abnormalities', covering 10 domains pertinent to laboratory and instrumental markers, indexes and neuropsychiatric dimension (cognitive, neurologic and psychiatric field), and 'life impact', covering 7 domains related to physical function (from both the perspective of the patient and the physician), pain and quality of life. Conclusion: Our study revealed great heterogeneity in the instruments derived from populations with NPSLE and none of these had high-quality evidence. This supports the need to develop and further validate a core domain set and outcome measurement instruments to promote clinical research in this field, enhancing comparability across studies.